Position Change and Early Ambulation Post-Trans-Femoral Coronary Angiography: A Systematic Review - Ms. Archana Pardeshi; Dr. Sadhana Adhyapak; Dr. Khurshid Jamadar (The Bioscan, 2025)
Background: Trans-femoral coronary angiography (TFCA) is a key diagnostic procedure for assessing coronary artery disease. Post-procedural care, particularly early ambulation and structured position changes is essential to minimize complications and enhance recovery. While prolonged bed rest has traditionally been recommended, emerging evidence suggests that early mobilization may improve patient comfort and reduce hospital stays. However, inconsistencies in clinical guidelines necessitate a systematic evaluation of its safety and efficacy. Aim: This systematic review is aiming the impact of early ambulation and position changes on pain reduction, vascular complications, and patient recovery outcomes post-TFCA. Method: Following PRISMA guidelines, we searched PubMed, Scopus, Web of Science, Cochrane Library, and Embase, including clinical trial registries. RCTs and quasi-experimental studies meeting predefined criteria were included. Risk of bias was assessed using RoB 2 for RCTs and the JBI Critical Appraisal Checklist for quasi-experimental studies. Results: Five studies (n=556) were included. Early ambulation and position changes significantly reduced pain, particularly between the 2nd and 8th hours post-procedure, and improved patient comfort while reducing pain medication dependence. No significant increase in vascular complications (hematoma, hemorrhage, thrombosis) was reported. Some studies indicated a lower incidence of urinary retention in the intervention group. Conclusion: Early ambulation and position changes post-TFCA are safe and effective, reducing pain and improving recovery without increasing complications. Findings support standardized mobility protocols to optimize post-procedural care, warranting further large-scale RCTs for broader implementation.